Influence of fish protein hydrolysate produced from industrial residues on antioxidant activity, cytokine expression and gut microbial communities in juvenile barramundi Lates calcarifer. Issue 97 (February 2020) - Siddik, Muhammad A.B.; Chaklader, Md Reaz; Foysal, Md Javed; Howieson, Janet; Fotedar, Ravi; Gupta, Sanjay K.
Abstract: The present study investigated the supplemental effects of tuna hydrolysate (TH) in poultry by-product meal (PBM) and dietary fishmeal (FM) diets on antioxidant enzymatic activities, gut microbial communities and expression of cytokine genes in the distal intestine of juvenile barramundi, Lates calcarifer . Fish were fed with fermented (FPBM + TH) as well as non-fermented PBM (PBM + TH) and FM (FMBD + TH) diets with 10% TH supplementation for 10 weeks. A basal diet prepared without TH supplementation served as control. The results showed that the activity of glutathione peroxidase was significantly higher in FPBM + TH than the control, while the malondialdehyde and catalase activities were unchanged. FPBM + TH diet significantly ( P < 0.05) upregulated the pro-inflammatory cytokines including IL-1β and TNF-α while considerable downregulation ( P < 0.05) was observed in the mRNA expression levels of anti-inflammatory cytokine, IL-10 in the distal intestine of fish. The 16SrRNA analysis using V3–V4 region evidenced the ability of FPBM + TH to modulate the distal intestinal gut microbiome, augmenting the richness of Firmicutes and Fusobacteria at at phylum level and Bacillus, Lactococcus and Cetobacterium at genus level. All these results have shown that fermented PBM with TH supplementation could improve the antioxidant capacity and inflammatory responses of juvenile barramundi while influencing the microbial communities at both phylum and genera levels. Highlights: Tuna hydrolysate supplemented fermented poultry by-product meal (FPBM) enhanced glutathione peroxidase activity and cytokine expression. Firmicutes and Fusobacteria were found abundant in the intestine of barramundi fed FPBM supplemented with tuna hydrolysate. These results may advance the use of fish protein hydrolysate in alternative protein feedstuffs for promoting fish health and immunity.